2020
DOI: 10.1002/1878-0261.12799
|View full text |Cite
|
Sign up to set email alerts
|

Genetic factors associated with cancer racial disparity – an integrative study across twenty‐one cancer types

Abstract: Based on an integrative analysis using genomic data of 21 cancer types from TCGA, we identified biological factors contributing to racial disparity in cancer: XKR9 gene expression is significantly associated with overall survival for all cancers combined as well as for several individual cancers, suggesting that XKR9 could be a novel drug target for cancer immunotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 61 publications
0
12
0
Order By: Relevance
“…As the principal polyphenol isolated from turmeric, curcumin exhibits many pharmacological effects such as anti‐inflammatory, antioxidant, antiapoptotic, and so on. [ 1,2 ] Furthermore, curcumin is also able to restrain the growth of various cancer cell lines in vitro, especially in lung cancer. [ 3‐5 ] However, low stability and bioavailability of curcumin limit its practical clinical application.…”
Section: Introductionmentioning
confidence: 99%
“…As the principal polyphenol isolated from turmeric, curcumin exhibits many pharmacological effects such as anti‐inflammatory, antioxidant, antiapoptotic, and so on. [ 1,2 ] Furthermore, curcumin is also able to restrain the growth of various cancer cell lines in vitro, especially in lung cancer. [ 3‐5 ] However, low stability and bioavailability of curcumin limit its practical clinical application.…”
Section: Introductionmentioning
confidence: 99%
“…The breakpoints were located at 8q13.3 and 15q26.2 and, and the Chromosome 8 breakpoint separates exons 2 and 3 of XKR9 . This gene is a cell membrane bound protein and a member of the Kell Blood Group complex subunit-related gene family [51]. Based on a National Library of Medicine Pubmed literature search during the submission of this manuscript, there were no articles describing functional studies of this gene.…”
Section: Resultsmentioning
confidence: 99%
“…Based on a National Library of Medicine Pubmed literature search during the submission of this manuscript, there were no articles describing functional studies of this gene. One recent article reported that XKR9 gene expression in cancer was associated with decreased overall survival [51]. In this report, Li et al used the TCGA genomic data from 21 cancer types and identified differential expressed genes in tumors originating from different ethnicities.…”
Section: Chromosome 8 Translocation In An Msi Crcmentioning
confidence: 99%
“…We used several different types of data obtained from TCGA: RNA-seq, protein expression, DNA methylation, and microRNA-seq, which have been used in our previous studies (Stewart, Luks, Roycik, Sang and Zhang 2013, Li, et al 2017, Shi, et al 2017, Li, et al 2020.…”
Section: Genomics and Epigenomics Data From The Cancer Genome Atlas (mentioning
confidence: 99%